PENGAPLIKASIAN SOFTWARE MICROSOFT OFFICE DALAM MENINGKATKAN TUGAS AKADEMIK SISWA/I SMK BINTANG NUSANTARA PONDOK AREN – TANGERANG SELATAN - Ahmad, Ahmad (JARI : Jurnal Pengabdian Kepada Masyarakat Republik Indonesia, 2025)
Microsoft Office Software Training is an important effort to improve students' academic abilities in the digital era. In this training, a seminar was held which aimed to introduce the main features of Microsoft Word, Excel and PowerPoint which can support the completion of academic assignments. Training methods include presentations, practical demonstrations, and question and answer sessions. The results of the training showed a significant increase in the participants' understanding and application of the software, which had a positive impact on the efficiency and quality of academic assignments completed. In addition, feedback from participants shows that this training provides additional motivation to use technology in the learning process. Thus, Microsoft Office Software training has proven to be effective in supporting student academic achievement. The development of technology today is an inevitability that must be faced by all groups, both educators and students. Computer programs or computer applications which are a technological development can be used to develop teaching materials at the educational level starting from kindergarten, elementary school and even university level. In implementing this PKM, we from the PKM Lecturer Team carry out training by way of seminars and direct training on the program delivered to students. It is hoped that by implementing this PKM, the results achieved in this community service activity are that students will be able to know how secure data is in files or computer application programs.